"BENEFITS OF USING MIND MAPS IN SCHOOL" - Djumayeva Feruza Tulkunovna (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Annotation:  Mind  mapping  is  a  visual  learning  tool  that  enhances  students' comprehension, memory retention, and creativity. This article explores the benefits of using mind maps in educational settings, including improved critical thinking, better note-taking, and enhanced writing skills. By analyzing scholarly research and expert opinions,  this  paper  highlights  how  mind  maps  can  transform  traditional  teaching methods into dynamic, engaging learning experiences.